2022
DOI: 10.4094/chnr.2022.28.2.142
|View full text |Cite
|
Sign up to set email alerts
|

Missed nursing care and its influencing factors among neonatal intensive care unit nurses in South Korea: a descriptive study

Abstract: Purpose: Preventing missed care is important in neonatal intensive care units (NICUs) due to neonates’ vulnerabilities. This study examined missed care and its influencing factors among NICU nurses.Methods: Missed care among 120 Korean NICU nurses was measured using a cross-culturally adapted online questionnaire. The frequency of missed care for 32 nursing activities and the significance of 23 reasons for missed care were collected.Results: All participants had missed at least 1 activity, missing on average 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…For instance, 93.2% of nurses missed providing neonatal developmental care, which was nearly the most frequently missed care, followed by supporting parents emotionally, which has been missed by 88.1% of NICU nurses. Similar to Gathara et al's (2019) [7] and Tubbs-Cooley et al's (2014) [8] findings, Kim and Chae (2022) also claimed that the involvement of parents in neonatal care and parents' education were missed by 83.1% of NICU nurses, which was found to be highly associated with decreased pain control levels and delayed discharge preparation [9]. In contrast with Gathara et al's (2019) study, Kim and Chae's (2022) study showed that assessing vital signs, providing feeding at the prescribed intervals, administering oxygen therapy, and adjusting oxygen concentration were among the least frequently missed nursing care tasks.…”
Section: Introductionsupporting
confidence: 78%
See 3 more Smart Citations
“…For instance, 93.2% of nurses missed providing neonatal developmental care, which was nearly the most frequently missed care, followed by supporting parents emotionally, which has been missed by 88.1% of NICU nurses. Similar to Gathara et al's (2019) [7] and Tubbs-Cooley et al's (2014) [8] findings, Kim and Chae (2022) also claimed that the involvement of parents in neonatal care and parents' education were missed by 83.1% of NICU nurses, which was found to be highly associated with decreased pain control levels and delayed discharge preparation [9]. In contrast with Gathara et al's (2019) study, Kim and Chae's (2022) study showed that assessing vital signs, providing feeding at the prescribed intervals, administering oxygen therapy, and adjusting oxygen concentration were among the least frequently missed nursing care tasks.…”
Section: Introductionsupporting
confidence: 78%
“…Similar to Gathara et al's (2019) [7] and Tubbs-Cooley et al's (2014) [8] findings, Kim and Chae (2022) also claimed that the involvement of parents in neonatal care and parents' education were missed by 83.1% of NICU nurses, which was found to be highly associated with decreased pain control levels and delayed discharge preparation [9]. In contrast with Gathara et al's (2019) study, Kim and Chae's (2022) study showed that assessing vital signs, providing feeding at the prescribed intervals, administering oxygen therapy, and adjusting oxygen concentration were among the least frequently missed nursing care tasks. A cross-sectional study conducted by Gathara et al (2019) on 216 neonates at six hospitals in Nairobi and Kenya concluded that the average completion rate of nursing tasks was 60%, which could adversely impact neonatal safety and outcomes.…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…Missed nursing care presents a global challenge with diverse implications, necessitating an understanding of clinical nurses' experiences (Alireza et al, 2022). Nurses' workload related to medication administration directly influences missed care, particularly in tasks involving developmental care that demand time and patience, often conflicting with prioritizing safety and encountering inadequate working conditions (Soohyun et al, 2022). The repercussions of missed nursing care extend to negative impacts on nurses' health, job…”
Section: Introductionmentioning
confidence: 99%